2021
DOI: 10.3390/sym13081505
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus Bilateral Landing after Spike Jumps in Male and Female Volleyball: A Systematic Review

Abstract: Background: The spike is a key action in volleyball, and the landing technique and its asymmetries are commonly associated with an increased risk of injury. Objectives: The aim of this systematic review was to assess how male and female volleyball players land (i.e., unilaterally, or bilaterally) after spike jumps in matches and analytical settings (field or laboratory). Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines were followed, with eligibility criteria defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Increase in echogenicity was associated with increased sRPE lagged while echogenicity of the non-dominant patellar tendon exhibited small and moderate negative associations with jump count and sRPE. Ground reaction forces upwards of 4× bodyweight can be experienced in a landing following an attack in volleyball (63) Attackers have been shown to prefer unilateral landing characterized by landing contact of the opposite side of the swing arm 68% of the time (64). The aforementioned findings may explain the observed inter-limb discrepancies in the current study and emphasize the need to develop more precise methods of measuring mechanical load (65).…”
Section: Patellar Tendon Structurementioning
confidence: 67%
“…Increase in echogenicity was associated with increased sRPE lagged while echogenicity of the non-dominant patellar tendon exhibited small and moderate negative associations with jump count and sRPE. Ground reaction forces upwards of 4× bodyweight can be experienced in a landing following an attack in volleyball (63) Attackers have been shown to prefer unilateral landing characterized by landing contact of the opposite side of the swing arm 68% of the time (64). The aforementioned findings may explain the observed inter-limb discrepancies in the current study and emphasize the need to develop more precise methods of measuring mechanical load (65).…”
Section: Patellar Tendon Structurementioning
confidence: 67%
“…In one match, male athletes landed on the left (31.5 percent) or right (8.5 percent) foot more than female athletes (23.7 percent and 1.6 percent). The study looked at spike landings that showed unilateral landings (mostly left foot first for right-handed players) in both men and women, but men more frequently [18].…”
Section: Discussionmentioning
confidence: 99%
“…Volleyball is known for its intricate and dynamic movements [11,12], requiring various physical attributes to enhance performance [13,14]. These essential attributes include coordination, balance, agility, strength, explosive power, flexibility, and reaction speed [3,15,16].…”
Section: Introductionmentioning
confidence: 99%